The autobiography of the young Carlos Monsiváis - Garfias Dávila, Marcos (2021)
The present essay deals with the autobiographical genre, to which great figures of literature, and also of politics and science, used to explain their trajectories. The essay focuses on the autobiography of Carlos Monsiváis, considered the «father of the modern chronicle in Mexico», unusually written in his youth.